Edukasi Masyarakat tentang Pentingnya Legalitas Usaha sebagai Penunjang Branding Produk - Syukur, Agus; Puspita, Ratna; Aulia, Nisrina Zahra; Diwani, Meftyane Liz; Bilqis, Shanaz Hafizah; Fitri, Qurrota A’yun Khoiriyyah (PT. Riset Press International, 2025)
This community service activity aims to improve the knowledge and skills of MSME actors in understanding